“They Steal Our Work”: Wage Theft and the Criminalization of Immigrant Day Laborers in Colorado, USA - Galemba, Rebecca Berke (European journal on criminal policy and research, 2021)
Latino immigrant day laborers are among the most vulnerable populations in the USA, frequently subject to work-related abuses such as wage theft in violation of federal and state labor laws. Despite legal reforms to facilitate wage recovery for low-wage workers and to recognize wage theft as a crime, this article draws on over two years of community-based research to show how day laborers face challenges mobilizing their legal rights and holding employers accountable for the crimes they suffer owing to their own criminalization and devaluation in US society. Contributing to harms-based approaches in critical criminology, it explores how individual legal remedies or criminal justice responses can risk obscuring the ways that wage theft is embedded along a continuum of legal and illegal exploitative labor practices that are normalized and maintained by the broader degradation of work and the criminalization of immigration.